Females of a polymorphic seabird dislike foreign-looking males - López-Rull, Isabel; Lifshitz, Natalia; Macías Garcia, Constantino; Graves, Jefferson Alden; Torres, Roxana (Animal Behaviour, 2016)
Sexual selection may facilitate speciation if it promotes divergence in attributes used in mate choice, causing prezygotic isolation between populations. Brown boobies, Sula leucogaster, are seabirds that can be grouped into four genetic clusters and two male plumage morphs: brown-headed sexually monomorphic and white-headed male dimorphic. The extent of white on the head (white hood) of a male may reflect parenting ability and be sexually selected. Colour morphs have been geographically isolated, but contact has been recently reported. We manipulated male hood colour in two dimorphic populations (at Islas Marietas National Park (hereafter Marietas), which is close to the contact zone of San Benedicto Island, and San Jorge Island, which is away from the contact zone) to establish whether female preference for male hoods can function as a reproductive barrier. Females from Marietas were more aggressive towards male mates whose white hoods were painted brown (allopatric-looking) than were females from San Jorge. Although experimental females from both islands courted less than females from control pairs, experimental females from Marietas were five times less likely to copulate than control females, whereas there were no differences between treatments in propensity to copulate by females in San Jorge. Thus, in the brown booby, female dislike of foreign males may function as a reproductive barrier in populations close to contact zones, where the risk of possibly maladaptive hybridization is highest. (C) 2016 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.